Photic zone euxinia during the permian-triassic superanoxic event - Grice, Kliti; Cao, C.; Love, G.; Bottcher, M.; Twitchett, R.; Grosjean, E.; Summons, R.; Turgeon, S.; Dunning, William; Jin, Y. (American Association for the Advancement of Science, 2005)
Carbon and sulfur isotopic data, together with biomarker and iron speciation analyses of the Hovea-3 core that was drilled in the Perth Basin, Western Australia, indicate that euxinic conditions prevailed in the paleowater column during the Permian-Triassic superanoxic event. Biomarkers diagnostic for anoxygenic photosynthesis by Chlorobiaceae are particularly abundant at the boundary and into the Early Triassic. Similar conditions prevailed in the contemporaneous seas off South China. Our evidence for widespread photiczone euxinic conditions suggests that sulfide toxicity was a driver of the extinction and a factor in the protracted recovery.